ANALISIS KELENGKAPAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PEKERJA BENGKEL LAS DI AUR BIRUGO KOTA BUKITTINGGI - Eka Trio Effandilus; Sri Mindayani; Rahmad Fajar (Bajang Institute, 2025)
The use of Personal Protective Equipment (PPE) in the informal sector is still low due to discomfort factors, increasing workers' vulnerability to accidents and occupational diseases. Based on data from 10 welding workshops, there are 2-3 work accidents each year due to not using PPE, such as burns, eye injuries, and hand injuries. This study aims to determine the factors related to the complete use of PPE in welding workers in Aur Birugo, Bukittinggi City. The type of research used is quantitative analytic with a cross-sectional design. This study was conducted from December 2023 to August 2024 in a welding shop in the Aur Birugo, Bukittinggi City. The sample in this study was 60 people used the total sampling technique. Data processing uses SPSS. Univariate and bivariate test analysis using the Chi Square test.The results analysis showed that 56.7% of welding workers had incomplete use of PPE, 55% of welding workers had low knowledge, 55% of welding workers had negative attitudes and 53.3% of welding workshop workers did not have PPE in the welding workshop. Bivariate analysis showed a relationship between the level of knowledge (p-value = 0.001), attitude (p-value = 0.003) and availability of PPE (p-value = 0.000) with the completeness of using Personal Protective Equipment (PPE) in welding workshop workers in Aur Birugo Bukittinggi City. It is recommended that considerations in proving complete PPE and increasing worker awareness of the impoetanace of using PPE